Tempering Transnational Advocacy? The Effect of Repression and Regulatory Restriction on Transnational NGO Collaborations. (31st July 2021) - Fransen, Luc; Dupuy, Kendra; Hinfelaar, Marja; Zakaria Mazumder, Sultan Mohammed
Abstract: This paper examines through qualitative study the effect of government regulatory restriction and repression on non‐governmental organizations (NGOs) engaging in transnational advocacy. The focus is on NGO's advocacy activities, in the realm of human rights, environment, labor and development in particular, using illustrations from Bangladesh and Zambia. It finds that next to some NGOs disbanding and moving towards service activities, many NGOs shift in terms of substantive advocacy and form of organizational collaboration. To continue cross‐border interactions with their foreign partners, many NGOs adjust to circumvent or compensate for restrictions and repression. Because of this, transnational advocacy can be said to continue, but repression and restrictions have significant substantive and organizational effects for the collaborations studied, and cross‐border NGO collaborations in our sample are increasingly fragile and their advocacy more tempered. Abstract : Our research found that most of the time, non‐governmental organization representatives themselves planned and enacted changes in their transnational collaborations as a response to pressures. Donors involved in sponsoring activities mostly accommodated these changes, and exercised flexibility.